2010
DOI: 10.1373/clinchem.2009.140202
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Uptake by Macrophage Cell Line via Class-A Scavenger Receptor

Abstract: BACKGROUND: C-reactive protein (CRP) increases in response to inflammation and is purported to be a risk factor for atherogenesis. We recently demonstrated that a scavenger receptor, lectin-like oxidized LDL receptor (LOX-1), is a receptor for CRP. In light of the overlapping ligand spectrum of scavenger receptors such as modified LDL, bacteria, and advanced glycation end products, we examined whether other scavenger receptors recognize CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
16
0
3
Order By: Relevance
“…FcαR [6], SR-A [7] and LOX-1 [8], thus giving CRP the potential to modulate the responses of immune and vascular cells. These characteristics lead to the consensus that CRP is an important component of the host defense and inflammation [1][2][3], despite the fact that the actual function of CRP remains to be clearly defined in an appropriate animal model [1,9,10].…”
mentioning
confidence: 99%
“…FcαR [6], SR-A [7] and LOX-1 [8], thus giving CRP the potential to modulate the responses of immune and vascular cells. These characteristics lead to the consensus that CRP is an important component of the host defense and inflammation [1][2][3], despite the fact that the actual function of CRP remains to be clearly defined in an appropriate animal model [1,9,10].…”
mentioning
confidence: 99%
“…Also like CRP, LOX-1 is produced in human atherosclerotic lesions. In recent work published in this journal, Fujita et al reported the exciting discovery that CRP actually binds to LOX-1 in vitro, and they provided evidence that this interaction also takes place in vivo (15,16 ). Thus, in a strain of rats that produces large amounts of LOX-1, intradermal injection of human CRP increased vascular permeability, and the effect could be suppressed by coadministration of an anti-LOX-1 antibody.…”
mentioning
confidence: 99%
“…21,24 . A expressão desse receptor LOX-1, também, é estimulada pela proteína C-reativa (PCR) 21,24 .…”
Section: Introductionunclassified
“…21,24 . A expressão desse receptor LOX-1, também, é estimulada pela proteína C-reativa (PCR) 21,24 . O processo de estresse oxidativo não só causa diminuição da produção de óxido nítrico, como também a mais disfunção endotelial 21 .…”
Section: Introductionunclassified
See 1 more Smart Citation